Pengaruh Faktor Psychosocial Safety Climate terhadap Safety Behavior di Perusahaan Pangan Pengolah Kecap dan Sirup - Maimunah, Dewi Rizqi; Kurniasih, Dewi; Rachman, Farizi (JURNAL UNITEK, 2025)
The high rate of occupational accidents in the food industry continues to be largely attributed to unsafe actions related to worker behavior. Within the context of food processing, which is inherently complex and high-risk, establishing a work environment that promotes psychosocial safety is crucial. Workers' perceptions of how well their organization prioritizes psychosocial safety may influence their compliance with and participation in workplace safety practices. This study aims to examine the influence of the psychosocial safety climate on safety behavior among assembling division workers in a soy sauce and syrup processing company. A quantitative research approach was employed using a survey method, with a validated and reliable questionnaire. A total of 70 permanent workers participated as respondents, and the data were analyzed using multiple linear regression with the aid of statistical software. The simultaneous test results indicated that psychosocial safety climate significantly affects safety behavior (p = 0.000). Partially, management support and commitment (p = 0.012), management priority (p = 0.000), and organizational communication (p = 0.001) had a significant positive influence on safety behavior. In contrast, organizational participation and involvement were found to be statistically insignificant (p = 0.628) and negatively associated. The coefficient of determination (R²) was 0.403, indicating that psychosocial safety climate explains 40.3% of the variance in safety behavior. These findings highlight the critical role of tangible management support, effective communication, and prioritization and involvement in fostering safe and sustainable workplace behavior.